The Impact of Combination Therapy Utilizing Citrus limon Aromatherapy and Mozart Classical Music Distraction Therapy to Reduce The Pain Intensity in Post-Sectio Caesarea Mothers - Novi Anggraeni; Nurun Nikmah; Selvia Nurul Qomari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Background: The pain intensity in sectio caesarea postpartum women remains the most difficult physical and emotional obstacle and also it has a direct impact in slower recovery rate. Different physical and non-physical therapies were implemented to reduce the pain and to speed up the recovery. The objective of this study is to assess the direct impact to the mothers after applying a combination therapy using lemon aromatherapy and Mozart classical music distraction therapy. Method: A total of thirty women aged between 18 and 37 years were included in this study with two sets of treatments. Fifteen corespondents received the treatments of lemon aromatherapy combined with Mozart classical mucis and the other fifteen obtained only deep breathing relaxation therapy (as control group). All treatments were applied for 15 minutes in one day. The level of pain intensity was measured before and after treatments. Result: After two sets of different treatments were applied to thirty of the corespondence women, the pain intensity was measured and analyzed. A Wilcoxon signed-ranked test indicated that the combination of lemon aromatherapy and Mozart classical music was efficient to reduce the pain in the subjects of this study (p<0.05). Additionally, based on the final scoring, the deep breathing exercise was less effective in lowering the pain compared to the combination of lemon aromatherapy and Mozart classical music albeit it differed significantly based on Mann-Whitney U non-parametric analysis (p< 0.05). Conclusion: A significant positive deviations in pain intensity was observed in section-caesarea postpartum women after receiving the combination treatments of lemon aromatherapy and Mozart classical music. Further studies that include prolonged follow-ups observation should be conducted to achieve an improved result